The effect of serum IL-2 levels on the prognosis of primary biliary cholangitis-related liver failure and the preliminary exploration of its mechanism - Wang, Qi; Wang, Yang; Qiao, Wenying; Xu, Bin; Liu, Yanmin; Zhang, Xiaodan; Li, Wenjuan; Zhao, Juan; Liu, Mengcheng; Zhang, Yang; Chen, Dexi; Huang, Chunyang; et al. (Frontiers in Immunology, 2022)
Background In primary biliary cholangitis (PBC), the levels of serum IL-2 were involved in liver inflammation and immune changes. This study aimed to investigate the prognostic significance of serum IL-2 combined with total bilirubin (TBIL) in liver failure and cytokine changes during the disease. Methods A total of 160 PBC patients treated with UDCA were included. Parameters at admission were collected, and the COX regression model was used to predict independent risk factors associated with PBC disease progression. We identified the optimal cut-off values and prognosis effects of serum IL-2 and TBIL based on the time-dependent receiver operating characteristic (ROC) curve. We also analyzed the incidence of liver failure with Kaplan-Meier survival analysis. In addition, the changes of cytokines (mainly IL-2) in liver tissues and blood samples from 11 patients with end-stage PBC liver failure and five healthy controls were examined. Results Age, IL-2, ALB, γ-GT, ALP, TBIL, Hb, TBA, WBC, and PLT, as well as anti-Sp100, were found to be independent risk factors in PBC patients with liver failure. Patients with decreased serum IL-2 levels and increased TBIL levels have a significantly higher incidence of liver failure and a worse prognosis. Patients with advanced PBC liver failure after liver transplantation exhibited a significant decrease in levels of serum IL-2 and a relatively immunosuppressed status. Conclusions The combination of serum IL-2 and TBIL can be a predictor of the progression of liver failure in patients with primary biliary cholangitis, and it is likely to be related to the expression of GM-CSF and G-CSF.